The coefficient of variation asymptotic in case of non-iid random variables - Curto, J.; Pinto, J. (Journal of Applied Statistics, 2009)
Due to the widespread use of the coefficient of variation in empirical finance, we derive its asymptotic sampling distribution in the case of non-iid random variables to deal with autocorrelation and/or conditional heteroskedasticity stylized facts of financial returns. We also propose statistical tests for the comparison of two coefficients of variation based on asymptotic normality and studentized time-series bootstrap. In an illustrative example, we analyze the monthly return volatility of six stock market indexes during the years 1990–2007.